2005
DOI: 10.1007/s00256-005-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided ablation of painful metastatic bone tumors: a new and effective approach to a difficult problem

Abstract: Painful skeletal metastases are a common problem in cancer patients. Although external beam radiation therapy is the current standard of care for cancer patients who present with localized bone pain, 20-30% of patients treated with this modality do not experience pain relief, and few further options exist for these patients. For many patients with painful metastatic skeletal disease, analgesics remain the only alternative treatment option. Recently, image-guided percutaneous methods of tumor destruction have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 58 publications
1
103
0
11
Order By: Relevance
“…Thermal methods for tumor treatment (radiofrequency, cryoablation) have become important palliative [2] and in some cases curative modalities [3,4]. A number of common clinical conditions appear to be good targets for this type of approach, but remain largely unexplored, awaiting future innovators.…”
Section: Growth Areas and Problems Related To Shifting Boundariesmentioning
confidence: 99%
“…Thermal methods for tumor treatment (radiofrequency, cryoablation) have become important palliative [2] and in some cases curative modalities [3,4]. A number of common clinical conditions appear to be good targets for this type of approach, but remain largely unexplored, awaiting future innovators.…”
Section: Growth Areas and Problems Related To Shifting Boundariesmentioning
confidence: 99%
“…The interstitial ultrasound applicators considered in this study are modeled as a linear array of 1-4 tubular ultrasound transducers (7 MHz, 1.5 mm outer diameter (OD), 5-15 mm length (L), 150-360° angular sectors) operated from within a water-cooled plastic catheter (1.89 mm inner diameter (ID), 2.4 mm OD). 14 3 MHz transducers (3.2 mm OD, 5 or 15 mm L) within a 4 mm ID, 4.5 mm OD catheter were also considered. It has been previously shown that acoustic heat deposition in soft tissue and bone from a cylindrical interstitial ultrasound source may be modeled as a radially divergent intensity pattern well-collimated to the length of the transducer 15,16 : (2) where is the ultrasound absorption coefficient (Np/m), is the transmission coefficient (unitless) calculated assuming normal incidence, 21 is the acoustic intensity on the transducer surface (W/m 2 ), is the transducer radius (m), is the radial distance from the transducer's axis (m), and is the ultrasound attenuation coefficient (Np/m).…”
Section: Methodsmentioning
confidence: 99%
“…2 Radiation, surgery, drugs, and thermal ablation have been applied in treatment of metastatic bone tumors, with external beam radiation as the standard of care. 3 Thermal ablation has been previously applied to treat bone tumors in the spine as well as the appendicular skeleton. 3 In some RF ablation, laser ablation, and cryoablation procedures with posterior wall destruction, gases injected into the spinal canal successfully displaced and insulated the spinal cord, preventing neurological damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 RF or laser thermal ablation also offers an alternative palliative therapy for localised and painful osteolytic metastatic lesions. 13 The reduction of pain that can be obtained improves the quality of life of patients with cancer, who often have multiple morbidities and a limited life expectancy. A multidisciplinary approach to the management of these patients is recommended to select the optimal treatment, including orthopaedic surgeons, neurosurgeons, medical and radiation oncologists and interventional radiologists.…”
Section: Radiofrequency Thermal Ablationmentioning
confidence: 99%